2018
DOI: 10.3390/polym10091027
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rare Earth Lanthanum Oxide in Polymeric Matrix Brake Composites to Replace Copper

Abstract: The main focus of current research in polymeric matrix brake composites is on searching out a replacement for copper, which has been recently proved to be a hazard to human health and the environment. In this paper, rare earth lanthanum oxide was explored for the replacement of copper in composites. The mechanism of the role of lanthanum oxide in brake composites to replace copper was analyzed. Four series of polymeric matrix brake composites with various amounts of copper (15, 10, 5 and 0 wt %) and rare earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…It was concluded that a combination produced better results when substituting copper. Kaikui Zheng et al (2018) studied the role of Lanthanum Oxide in friction composites as a replacement of copper. Five composites were developed by replacing copper in compensation to Lanthanum Oxide in a range of 0 to 15 Wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that a combination produced better results when substituting copper. Kaikui Zheng et al (2018) studied the role of Lanthanum Oxide in friction composites as a replacement of copper. Five composites were developed by replacing copper in compensation to Lanthanum Oxide in a range of 0 to 15 Wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the particle size of table 3, the effect of La grain refinement can improve the hardness of the material. Zhang et al [27] studied the mechanical properties of Cu composites, and the hardness of the composites showed a significant improvement, from 135 HV to 140 HV, mainly due to the addition of La to refine and disperse other particles. Fu et al [28] studied the effect of La 2 O 3 on the microstructure and properties of Cu alloys, and found that when the content of La 2 O 3 increased to 0.2%, the hardness reached a maximum.…”
Section: Microscopic Morphology Analysis Of the Compositesmentioning
confidence: 99%
“…Composite friction materials, particularly those that are used in braking applications, generally contain four major components: binders, reinforcement fibers, fillers, and friction modifiers [ 9 , 10 , 11 , 12 , 13 ]. The binders are a major constituent and are used to maintain system integrity so that the composite friction materials can display the desired performance outcome while also maintaining key tribological properties (e.g., coefficient of friction and wear rate) and thermal stability.…”
Section: Introductionmentioning
confidence: 99%